The Effect of Parents’ Parenting Style on the Fourth-Grade Natural Science Students’ Learning Motivation at Elementary School - Harniwati Halawa; Bogor Lumbanraja; Patri Janson Silaban; Dewi Anzelina; Anton Sitepu (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper explains the effect of parents’ parenting style on natural science students’ motivation. The research was conducted in class IV at SD Negeri Medan Johor. The researchers used associative quantitative research methods. The population used was 36 fourth-grade students at SD Negeri 060938 Medan Johor. Sampling used total sampling (saturated sampling). The research results indicate that the results obtained from the correlation test can be seen in the correlation coefficient of rcount 0.97 ≥ rtable 0.329, hence it can be concluded that the alternative hypothesis (Ha) is accepted, it means that there is an effect of parents’ parenting style on students’ learning motivation at SD Negeri 060938 Medan Johor. It can also be seen from the t-test results where tcount 25.73 ≥ ttable 2.030, hence the hypothesis (Ha) is accepted. It shows that there is a positive significant effect between the effect of parents’ parenting style and natural science students' learning motivation in class IV at SD Negeri Medan Johor in the academic year 2022/2023.